Characterization of column chromatography separated bio-oil obtained from hydrothermal liquefaction of Spirulina. (1st August 2021) - Han, Jiahui; Li, Xing; Kong, Shengyan; Xian, Guang; Li, Hualong; Li, Xun; Li, Jie; Zhang, Jinglai; Meng, Han; Wang, Huansheng; Du, Hongbiao; Zeng, Fangang
Graphical abstract: Highlights: A new method for separating complex bio-oil was developed. Detected components increased from 25 to 109 after CCS process. HHVs increased from 31.83–36.04MJ.kg −1 to 38.32-42.19MJ.kg −1 after CCS process. Tert -hexadecanethiol was used as one of sulphur-contained model compound and its formation mechanism was speculated. Abstract: Bio-oil contained a large number of macromolecular compounds like asphalt, which made it difficult to obtain accurate results from direct test analysis. In this study, hydrothermal liquefaction (HTL) bio-oil of Spirulina (300 °C, 30 min, 10 MPa) was underwent column chromatography separation (CCS) process to retain the macromolecular substances in the column, which improved the accuracy of subsequent analysis results. The obtained fractions were characterized by Thermo-Gravimetric Analysis (TG), Gas Chromatography-Mass Spectrometry (GC-MS) analysis, Elemental Analysis, and Fourier Transform Infrared (FT-IR) Spectroscopy Analysis. TG analysis showed that a significant amount of components coexisting in high-boiling-range residue in bio-oil could be isolated into quasi-gasoline and quasi-kerosene species, so the low boiling-point fractions of bio-oil between 30-250 °C increased. GC-MS proved that CCS could effectively separate bio-oil and the number of detected components in bio-oil increased from 25 to 109 after CCS. The results of elemental analysis and FT-IR indicated that the components of the bio-oil were separated according to the polarity, and the higher heating values(HHVs) of each distillate oil (38.32-42.19 MJ kg −1 ) was significantly higher than the bio-oil before CCS (31.83-36.04 MJ kg −1 ). Comprehensive results of multiple analysis could help determine the market application prospects of bio-oil. In addition, tert -hexadecanethiol was studied as a representative Sulphur-compound to surmise its generation mechanism. The speculation of the conversion pathway of sulphur (S) element could provide a basis for a better understanding of the HTL reaction mechanism.